The Role of Sexual Education in Increasing Awareness of Early Childhood - Amalya, Meyfa Nur Alfu Laila (Maliki Interdisciplinary Journal, 2025)
To increase awareness of children's safety and welfare, sexual education in early childhood is important. This research looks at how sexual education can help young children become more aware and protect them from sexual violence. According to a literature review and analysis of data from various sources, including books, articles, and journals, sexual education starting early can help children understand and appreciate their own bodies, identify signs of danger, and avoid unsafe situations. Good sexual education can also improve a child's self-confidence and self-esteem, resulting in better relationships with others. This study shows that parents and educators are very important in providing age-appropriate and understanding sexual education to children.